(untitled) (Plant Bulletin, 2024)
Soil salinity is one of the significant issues in crop production and its adverse effects have been noticed at various stages of a crop life cycle therefore to assess the remedies for mitigation of soil salinity, the present study was conducted in Khipro district, Sanghar, Sindh, Pakistan during 2018-19. The experiment was laid out in Randomized Complete Block Design (RCBD), to evaluate the growth and yield responses of maize to different tillage practices and straw incorporation under different levels of gypsum in a saline-sodic soil. The factorial study was consisted of three factors including: Tillage practices (shallow tillage [ST] and deep tillage [DT], Wheat straw incorporation (3, 7, and 10 ton. ha-1) and gypsum rates (13.5, 9 and 4.5-ton ha-1). The comparative results showed that Deep Tillage DT with wheat straw incorporation at 10-ton ha-1 (DTWS10) had significantly higher result in term of growth and yield traits followed by shallow tillage ST at 10-ton ha-1 (STWS10). Moreover, the lowest results regard growth and yield attributes were observed in Shallow tillage ST with no wheat straw incorporation (STCK) Additionally, It was also observed that gypsum application did not have significant effect (P > 0.05) on maize growth and yield, but it mitigated soil salinity and sodicity, contributing to improved crop growth and yield. Therefore, incorporating straw into saline-sodic soils can significantly (P < 0.05) enhance maize yield and its attributes, with notable effects observed after two years of treatment.